BIOSECURITY PENUNJANG LIVELIHOOD MASYARAKAT KANIKE, SERAM UTARA, MALUKU - Nahumury, Glen A.F.; Ndoen, Marthen L. (Universitas Kristen Satya Wacana, 2017)
By relying on the people's livelihood through agricultural processed is certainly result on a threat to crop farmers, for it is important in applying the concept of biosecurity in an effort to protect the biological durability. Kanike community that exist in isolated conditions shall protect their biological resilience by not using pesticides and other chemicals, but applied on using secondhand materials, leaves and also the application of traditional values in society. This concept come out from the local knowledge of they community based of local wisdom. This local wisdom has gone over generations on them because of the legacy from the ancestors, the inheritance that happen through knowledge sharing and also experience in observing the process undertaken by their ancestors, in this way greatly help the Kanike community who is still in isolated area to maintain their sustainable livelihood.